Endodontic Management of Mandibular First Molar with Four Roots - A Rare Case Report with Clinical Management Guidelines - Shahbaz, Shaikh; Iftekhar, Huma; Alam, Sharique; Shavez, Zehra (UI Scholars Hub, 2022)
Mandibular molar is usually two rooted with one mesial and one distal root. Additional roots are rare which requires accurate diagnosis and a methodical and scrupulous endodontic treatment. Objective: This paper aims to report the endodontic management of an unusual case of a mandibular permanent first molar with four roots (two mesial & two distal) and provide a clinical guideline to detect and manage these variant cases. Case report: A 15-year-old boy reported with a deep carious lesion in the lower left first molar (#36). The apical root contour of #36 on an intraoral periapical radiograph taken in different angulations suggested the presence of extra roots. A Spiral Computed Tomographic scan with multiplanar three-dimensional reconstructed images confirmed a fourrooted mandibular molar. Endodontic treatment of #36 was planned based on a diagnosis of pulpal necrosis with symptomatic apical periodontitis. The pulp chamber floor was assiduously explored along the developmental root fusion line (DRFL) to guide a trapezoidal access cavity and expose two mesial and two distal orifices. Conclusion: The present case report highlights the successful endodontic treatment of an atypical four rooted mandibular first molar by following a systematic approach from diagnosis to its clinical management.